Quantitative Analysis of 5-Hydroxymethylfurfural in Linezolid Injection by High Performance Liquid Chromatography - Batista, Jéssica Maurício; Fernandes, Christian (Current Pharmaceutical Analysis, 2020)
Background: Linezolid is a synthetic broad-spectrum antibacterial belonging to the class of oxazolidinones. Linezolid for intravenous infusion is isotonized with dextrose. In acidic environment, the dehydration of dextrose produces furan derivatives, 5-hydroxymethylfurfural (5-HMF) being the main one. The determination of this degradation product is of fundamental importance, since there is evidence it is cytotoxic, genotoxic, mutagenic and carcinogenic. However, there is no official method for the determination of 5-HMF in drug products. Objective: The aim of this study was to develop and validate a high performance liquid chromatographic method to quantify 5-HMF in injection of linezolid. Methods: The chromatographic separation, after optimization, was performed on C18 (150 x 4.6 mm, 5 μm) column. Mobile phase was composed of 14 mM potassium phosphate buffer pH 3.0 ([H+] = 1.0 x 10-3) and methanol in gradient elution at 1.0 mL min-1. The injection volume was 10 μL and detection was performed at 285 nm. Results: The method was optimized and validated, showing selectivity, linearity in the range from 0.075 to 9.0 μg mL-1, precision (RSD ≤ 2.0%), accuracy (mean recovery of 100.07%) and robustness for temperature and pH variation. Conclusion: The method was shown to be adequate to determine 5-HMF in injection containing linezolid in routine analysis.
Keywords: high performance liquid chromatography